2020
DOI: 10.1109/access.2020.2966595
|View full text |Cite
|
Sign up to set email alerts
|

CASA: An Architecture to Support Complex Assessment Scenarios

Abstract: The evaluation or assessment of student performance and knowledge is a central element of most instructional design models, as it provides the information required to take remediation actions and improve the learning process. However, the assessment contexts present such a diverse range of cases due to course, teacher and student idiosyncrasies that it is difficult to support all the possibilities via software. To deal with this problem, this paper presents an architecture that satisfies the requirements to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In this order, one category of the research works reported in this study is devoted to the definition of new data sources for LA (see Table 7). These works explore the use of human-generated data like grades (Villamañe, Alvarez, & Larrañaga, 2020) or information provided by teachers in the learning design (Rodríguez-Triana, Martínez-Monés, Asensio-Pérez, & Dimitriadis, 2015); biometric signals captured with sensors (de Arriba-Pérez, Caeiro-Rodríguez, & Santos-Gago, 2018); or multimodal data including both self-reported and sensor-based data (Vujovic & Hernández-Leo, 2019). Some of these works are exploratory, and are aimed at identifying indicators for learning based on new data sources or at defining better learner models.…”
Section: Multimodal and Contextual Datamentioning
confidence: 99%
“…In this order, one category of the research works reported in this study is devoted to the definition of new data sources for LA (see Table 7). These works explore the use of human-generated data like grades (Villamañe, Alvarez, & Larrañaga, 2020) or information provided by teachers in the learning design (Rodríguez-Triana, Martínez-Monés, Asensio-Pérez, & Dimitriadis, 2015); biometric signals captured with sensors (de Arriba-Pérez, Caeiro-Rodríguez, & Santos-Gago, 2018); or multimodal data including both self-reported and sensor-based data (Vujovic & Hernández-Leo, 2019). Some of these works are exploratory, and are aimed at identifying indicators for learning based on new data sources or at defining better learner models.…”
Section: Multimodal and Contextual Datamentioning
confidence: 99%